Report of joint hypermobility in malignant hyperthermia susceptible patients: Observational study with a case-control descriptive design - Rita CCS. Santos; Larissa FCDMS. Lima; Pâmela V. Andrade; Joilson M. Santos; Leonardo Galleni; Antonio FR. Junior; Lucas S. Souza; Beny Schmidt; Acary SB. Oliveira; José LG. Amaral; Mariz Vainzof; Helga CA. Silva (Heliyon)
Background: Hypermobility is the capacity to perform joint movements in amplitudes greater than normal. Hypermobility is present in nearly 100 % of congenital myopathy central core disease (CCD) patients but is sporadically described in the allelic disease malignant hyperthermia (MH). Our objective was to investigate the frequency/characteristics of hypermobility in MH susceptible patients as compared to a control group, aiming the identification of correlations between hypermobility and demographic/clinical findings in MH patients. Methods: We recruited 26 MH patients (MH history, positive in vitro contracture test (IVCT), no muscle weakness, no cores in muscle biopsy) and 23 controls (no MH/myopathy history). Patients/medical records were evaluated for obtaining demographic/clinical data. Hypermobility was assessed in all patients and controls with Bulbena score. Goniometry was performed in a subset of 11 patients and 11 controls. Results: Bulbena score indicative of hypermobility was significantly more frequent in MH than in the control group (50 % versus 13 %, relative risk 2.06 (95%CI 1.27–3.35), chi-square test, p < .01). Goniometric assessment revealed significantly greater range of motion of mostly proximal movements in MH versus control groups. In the MH group, there was no correlation of the Bulbena score with age, sex, clinical complaints of myalgia/cramps, CK levels, IVCT result, or degree of contracture after caffeine or halothane. Conclusions: It is possible that predominantly proximal hypermobility is part of a clinical spectrum associated with RYR1 gene variants, as it was present even when associated muscle weakness was not present. More studies are necessary to measure evolution and long-term impact of hypermobility in MH patients.